Bayesian networks in forensic identification problems - Andrade, M.; Ferreira, M. A. M. (Aplimat - Journal of Applied Mathematics, 2009)
Paternity dispute and criminal identification problems are examples of situations in which forensic approach the DNA profiles study is a common procedure. In order to deal with the problems mentioned it is needed an introduction to present and explain the various concepts involved, since distinct areas must be considered. In the second paragraph some problems are presented. Here it is exhibited an algebraic treatment, for the simpler problems and with those the use of the object-oriented Bayesian networks is shown. Then the most complex kind of problems that may occur is presented. In the last paragraph some comments are added.